(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the articulatory and acoustic features that contribute to human speech production, focusing on the functions and interactions of the speech organs. The articulatory features section breaks down how different places and manners of articulation, such as bilabials, velars, stops, and fricatives, shape specific sounds. The discussion on acoustic features introduces key properties like frequency, amplitude, formants, and duration, which define the auditory characteristics of speech sounds and affect their perception. Additionally, the article details the anatomical components involved in producing speech, including the lungs, larynx, pharynx, oral and nasal cavities, tongue, teeth, and lips. Each of these speech organs contributes uniquely to articulating sounds and influencing acoustic qualities, ultimately enabling complex, varied, and nuanced human communication. The article concludes by emphasizing the importance of understanding these mechanisms for fields such as linguistics, speech therapy, and technology, highlighting how insights into the articulatory and acoustic bases of speech deepen our knowledge of language and communication. This comprehensive approach offers a foundation for studying and addressing the intricacies of human speech in both practical and theoretical contexts.